Assessment of sensitivity, specificity and species discriminatory power of four culture-based isolation methods of Arcobacter spp - Hussain Shah, Sayed Atta; Abdul Aziz, Saleha; Marimuthu, Murugaiyah; Zakaria, Zunita (Academic Journals, 2011)
A total of 142 samples including beef (n = 52), fresh milk (n = 45) and rectal swabs of cattle (n = 45) were collected from various wet markets (beef) and dairy cattle farms (milk and rectal swabs) in the vicinity of Selangor, Malaysia. All samples were examined for the presence of Arcobacter species using four different isolation methods. The organisms were first identified on the basis of phenotypic tests and later the suspected isolates were confirmed using multiplex PCR (mPCR). Method I (MI) and Method II (MII) detected Arcobacter in 43.7 and 75%, respectively from beef, but were unable to detect microbe from milk and rectal swabs. On the other hand, Method III (MIII) detected Arcobacter in 100, 60 and 40% of beef, milk and bovine rectal swab samples respectively; Method IV (MIV) detected 93.7, 60 and 40% in beef, milk and cattle rectal swabs respectively. The discriminatory power among the isolation methods for Arcobacter species was evaluated and MIII was found to be the best as it identified A. butzleri (72.7%); A. cryaerophilus (22.7%) and A. skirrowii (4.5%) while A. butzleri (61.1%), A. cryaerophilus (22.7%) and A. skirrowii (9%) were isolated from MIV.